The exchange university : corporatization of academic culture - Fisher, Donald, 1944-; Chan, Adrienne S. (UBC Press, 2008)
"The Exchange University addresses crucial questions facing today's university, including the commercialization of research and teaching; intensifying government-university relationships; marketization and commodification; and policy and functional responses within the academy. The book will interest practitioners, students, and academics in educational studies, policy studies, and higher education."--Jacket.